2018
DOI: 10.1080/14786419.2018.1440223
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial substances from the rare actinomycete Nonomuraea rhodomycinica NR4-ASC07T

Abstract: Nonomuraea rhodomycinica NR4-ASC07 is a rare actinomycete isolated from soil in Sirindhorn peat swamp forest. The crude extract of its culture broth exhibited antimicrobial and anticancer against diverse human pathogens and cancer cells. The chemical investigation of the crude extract led to the isolation of two new metabolites named nonomuric acid (1) and 3-hydroxy deoxydaunorubicinol aglycone (2), along with two known bioactive compounds [ε-rhodomycinone (3) and 7-deoxy-13-dihydrocarminomycinone (4)]. Compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Meanwhile, compound 103 displayed inhibitory activity against Mycobacterium tuberculosis and Bacillus cereus with MIC values of 50.0 and 12.50 mg mL À1 , respectively. 32 Madurahydroxylactone 104, as a new inhibitor of Staphylococcus aureus FtsZ, and its derivatives 105-108 have been obtained from Nonomuraea sp. AN100570 from soil collected near Gongju city, Korea.…”
Section: Secondary Metabolites From Nonomuraeamentioning
confidence: 99%
“…Meanwhile, compound 103 displayed inhibitory activity against Mycobacterium tuberculosis and Bacillus cereus with MIC values of 50.0 and 12.50 mg mL À1 , respectively. 32 Madurahydroxylactone 104, as a new inhibitor of Staphylococcus aureus FtsZ, and its derivatives 105-108 have been obtained from Nonomuraea sp. AN100570 from soil collected near Gongju city, Korea.…”
Section: Secondary Metabolites From Nonomuraeamentioning
confidence: 99%
“…These results matched with that of Tsuji et al [35] which showed that γ-rhodomycinone, had no differentiation inducing activity, but was cytotoxic however, this cytotoxicity activity against normal cell lines was much lower than cancer cell lines. Supong and his co works recently showed that εrhodomycinone produced by a rare actinomycete Nonomuraea rhodomycinica NR4-ASC07 has a potential antimalarial activity [36]. Further studies should be conducted to explore the biosynthetic pathways of the respective metabolites as well as to produce new derivatives of the anthracycline family with higher antitumor activities and lower side effects.…”
Section: Discussionmentioning
confidence: 99%
“…These results matched with that of Tsuji et al [35] which showed that γ-rhodomycinone, had no differentiation inducing activity, but was cytotoxic however, this cytotoxicity activity against normal cell lines was much lower than cancer cell lines. Supong and his coworks recently showed that εrhodomycinone produced by a rare actinomycete Nonomuraea rhodomycinica NR4-ASC07 has a potential antimalarial activity [36]. Further studies should be conducted to explore the biosynthetic pathways of the respective metabolites as well as to produce new derivatives of the anthracycline family with higher antitumor activities and lower side effects.…”
Section: Discussionmentioning
confidence: 99%